Evaluation of Streamflow Drought Index in Aegean Region, Turkey - Gulmez, Ayse; Mersin, Denizhan; Vaheddoost, Babak; Safari, Mir Jafar Sadegh (Springer International Publishing Ag, 2022)
Water is an invaluable substance of which ensures the life cycle and hydrological events across the world. In this respect, water deficit also known as drought is a natural disaster related to water scarcity in time and space. Although there is no solid definition for the phenomenon, the outcome of repeated wet and dry spells cause in economic, social, and political problems at regional, country-wide, and world-wide scale. In this study, drought associated with the streamflow in the Aegean region, which has an important economic, historical and wsocio-cultural role in the western Turkey, is investigated through the well-known streamflow drought index (SDI). Therefore, average discharge in the Cicekli-Nif, Besdegirmenler-Dandalas, Bebekler-Rahmanlar and Kocarli-Koprubasi station respectively related to on Gediz, Buyuk Menderes and Kucuk Menderes basins were used. Then SDI with 1, 3, 6,12 months moving average are acquired to express the drought severity associated with the streamflow in the basins. Results showed that the SDI values in all of stations together with the 1, 3, 6, and 12-month moving averages depicts similar results and no abnormal situation exist during the study period.
5th International Conference on Natural Resources and Sustainable Environmental Management -- NOV, 2021 -- Near E Univ, Nicosia, CYPRUS
Keywords: Aegean region; Drought; Streamflow drought index; Hydrology